THE USE OF ELECTRONIC-BASED EDUCATIONAL GAME TOOL "SMART HAFIZ" IN STIMULATING EARLY CHILDHOOD DEVELOPMENTIN THE PANDEMIC ERA - Sofia Rizki Julianti; Erni Munastiwi (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
Problems that occur during pandemics, especially in early childhood education, begin when the learning system is implemented at home. Early childhood needs special attention in its development, requires assistance and fulfillment of its needs during the pandemic, including the procurement of facilities that support children's learning. This study aims to examine the electronic-based educational game tool "Smart Hafidz" which is expected to present as a solution to learning problems that occurred during the pandemic. This type of research uses a qualitative approach through review literature, with study and look at existing literature related to this research. Based on the results of this study, the presence of several educational game tools, one of which is Smart Hafidz can be used as one of the problems in stimulation early childhood development during the pandemic. Stimulation through Smart Hafidz contained in the development of art, language, and most importantly the development of moral and religious values.